White-Light Emission from Single-Material ZnSe-Based Quantum Dots Synthesized under Aqueous Conditions - Kim, Jea Hyung; Lee, Ji Hyeon; Hong, Hyun Seon (Archives of Metallurgy and Materials, 2026)
Quantum dots (QDs) are promising luminescent materials due to their tunable bandgaps and high color purity. White-light emission was achieved using ZnSe-based QDs synthesized under low-temperature aqueous conditions. ZnSe/ZnS, Cu-doped ZnSe/ZnS, and Mn-doped ZnSe/ZnS QDs prepared in deionized water at 90°C exhibited blue, green, and orange emissions, respectively. A ZnS shell enhanced optical stability, and white light was realized by physically mixing single-family QDs with different dopant centers. Optimized mixing of peaks at 370, 514, and 578 nm produced a broad spectrum ( 350–580 nm), and a 1:5:6 mixture yielded chromaticity coordinates near the CIE D65 white point. This study demonstrates a simple and effective approach for white-light generation using aqueous-synthesized ZnSe-based QDs.